2002
DOI: 10.1029/2001jd002048
|View full text |Cite
|
Sign up to set email alerts
|

Quantum yields of O(1D) formation in the photolysis of ozone between 230 and 308 nm

Abstract: Ozone molecules are photolyzed in the strong photoabsorption band of the Hartley band at 230–308 nm, and the O(3Pj) photofragments produced by the photolysis are detected directly by a technique of laser‐induced fluorescence around 130 nm. The quantum yield values for O(1D) formation in the photolysis of ozone at 297 ± 2 K are determined as a function of the photolysis wavelength, using the O(1D) quantum yield value of 0.79 at 308 nm as a reference. The O(1D) quantum yield values obtained are found to be almos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
42
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(46 citation statements)
references
References 30 publications
(56 reference statements)
4
42
0
Order By: Relevance
“…Talukdar et al (1998) reported that the O( 1 D) quantum yield between 289 and 305 nm was 0.89±0.02, which is in good agreement with results presented by Taniguchi et al (2000) and Takahashi et al (2002). The yield values reported by Trolier and Wiesenfeld (1988) and JPL-2000 recommendations in this wavelength region are larger than values reported by Talukdar et al (1998) , Taniguchi et al (2000), and Takahashi et al (2002). At shorter wavelengths, JPL-2000 panel has recommended a constant value of 0.95 for the O( 1 D) quantum yield in the Hartley band photolysis of O 3 between obtained by Taniguchi et al (2000) and Takahashi et al (2002).…”
Section: Introductionsupporting
confidence: 81%
See 4 more Smart Citations
“…Talukdar et al (1998) reported that the O( 1 D) quantum yield between 289 and 305 nm was 0.89±0.02, which is in good agreement with results presented by Taniguchi et al (2000) and Takahashi et al (2002). The yield values reported by Trolier and Wiesenfeld (1988) and JPL-2000 recommendations in this wavelength region are larger than values reported by Talukdar et al (1998) , Taniguchi et al (2000), and Takahashi et al (2002). At shorter wavelengths, JPL-2000 panel has recommended a constant value of 0.95 for the O( 1 D) quantum yield in the Hartley band photolysis of O 3 between obtained by Taniguchi et al (2000) and Takahashi et al (2002).…”
Section: Introductionsupporting
confidence: 81%
“…The yield values reported by Trolier and Wiesenfeld (1988) and JPL-2000 recommendations in this wavelength region are larger than values reported by Talukdar et al (1998) , Taniguchi et al (2000), and Takahashi et al (2002). At shorter wavelengths, JPL-2000 panel has recommended a constant value of 0.95 for the O( 1 D) quantum yield in the Hartley band photolysis of O 3 between obtained by Taniguchi et al (2000) and Takahashi et al (2002). For comparison, the yield values reported by other groups are also shown (Trolier and Wiesenfeld, 1988;Cooper et al, 1993;Talukdar et al, 1997Talukdar et al, , 1998.…”
Section: Introductionmentioning
confidence: 46%
See 3 more Smart Citations